Distinct Functional Properties of Isoamylase-Type Starch Debranching Enzymes in Monocot and Dicot Leaves(1)([C])([W])([OPEN]) - Facon, Maud (American Society of Plant Biologists, 2013)
Isoamylase-type starch debranching enzymes (ISA) play important roles in starch biosynthesis in chloroplast-containing organisms, as shown by the strict conservation of both catalytically active ISA1 and the noncatalytic homolog ISA2. Functional distinctions exist between species, although they are not understood yet. Numerous plant tissues require both ISA1 and ISA2 for normal starch biosynthesis, whereas monocot endosperm and leaf exhibit nearly normal starch metabolism without ISA2. This study took in vivo and in vitro approaches to determine whether organism-specific physiology or evolutionary divergence between monocots and dicots is responsible for distinctions in ISA function. Maize (Zea mays) ISA1 was expressed in Arabidopsis (Arabidopsis thaliana) lacking endogenous ISA1 or lacking both native ISA1 and ISA2. The maize protein functioned in Arabidopsis leaves to support nearly normal starch metabolism in the absence of any native ISA1 or ISA2. Analysis of recombinant enzymes showed that Arabidopsis ISA1 requires ISA2 as a partner for enzymatic function, whereas maize ISA1 was active by itself. The electrophoretic mobility of recombinant and native maize ISA differed, suggestive of posttranslational modifications in vivo. Sedimentation equilibrium measurements showed recombinant maize ISA1 to be a dimer, in contrast to previous gel permeation data that estimated the molecular mass as a tetramer. These data demonstrate that evolutionary divergence between monocots and dicots is responsible for the distinctions in ISA1 function.